Respostas
respondido por:
5
Use delta e Bhaskara para resolver essa equação:
Delta: b(ao quadrado) - 4.a.c
Bhaskara:-b +- raiz de delta/2.a
Delta: b(ao quadrado) - 4.a.c
Bhaskara:-b +- raiz de delta/2.a
respondido por:
43
a=1 b=-13 c=36
X1= (-b+√Δ)/2a
X1=(-b+√b-4ac)/2a
X1=(-(-13)+√(13)²-4.1.36)/2.1
X1=(13+√25)/2
X1=(13+5)/2
X1= 18/2=9
X2= (-b-√Δ)/2a
X2=(-b-√b-4ac)/2a
X2=(-(-13)-√(13)²-4.1.36)/2.1
X2=(13-√25)/2
X2=13-3/2=4
X1= (-b+√Δ)/2a
X1=(-b+√b-4ac)/2a
X1=(-(-13)+√(13)²-4.1.36)/2.1
X1=(13+√25)/2
X1=(13+5)/2
X1= 18/2=9
X2= (-b-√Δ)/2a
X2=(-b-√b-4ac)/2a
X2=(-(-13)-√(13)²-4.1.36)/2.1
X2=(13-√25)/2
X2=13-3/2=4
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás